Expression of HK2 Gene is Deregulated in Prostate Cancer - Kudryavtseva, Anna Viktorovna (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: Prostate cancer (PC) is the second most common cancer in men. Therefore, the search for genes that could be potential targets for therapy as well as diagnostic and prognostic markers is an important task. Materials and Methods: In this work, the expression of genes encoding the enzymes of the first stage of glycolysis, hexokinases (HK1, HK2, and HK3), was analyzed by quantitative polymerase chain reaction (qPCR). Results: In 35% of PC samples, up to 7-fold increase was revealed in the expression of the HK2 gene, whereas in 15% of cases, up to 5-fold decrease was observed. The HK1 mRNA level was unchanged in most of the examined samples. The HK3 expression was very low and could not be detected by qPCR. Conclusion: Thus, obtained results indicate that the activation of glycolysis in PC is likely caused by the HK2 upregulation. The increased mRNA level of HK2 gene could be a marker of this process in PC.